Futurology in the College Classroom - Skylar Davidson (Park University, 2017)
There is little research on teaching futurology, which is surprising, given that instructors with a future-oriented perspective can encourage students to express constructive hope about controversial problems (e.g., climate change) rather than denying problems (Ojala, 2015). This study evaluates what learning outcomes can be accomplished through three different future-oriented in-class group activities: a future-oriented discussion, a future-oriented roleplay activity, and a backcasting activity. Analysis of student feedback suggests that these three activities encourage similar levels of student interest, understanding, and productive discussion while helping students practice both general college skills and skills specifically related to futurology. The main strength of future-oriented discussion is general understanding of both a topic and one's own perspective on it; of future-oriented roleplay, debate and emotional engagement; and of backcasting, evaluation of different potential futures and a sense of ownership over the future.